Experimental study on the tensile and bending creep behavior of cracked UHP-FRCC - Nishiwaki, T.; Otaki, H.; Igarashi, G.; Kwon, S.; Shaikh, Faiz; Fantilli, A. (2017)
Ultra-High-Performance Fiber-Reinforced Cementitious Composite (UHP-FRCC) shows very high strength and durability due to its very dense microstructure. While extensive research on the tensile and bending behavior of this composite under short-term loading has been reported, limited results are available on the time dependent behavior of UHP-FRCC under sustained loading, which are strongly related to the real-life-structures. This paper presents experimental results concerning creep behavior of cracked UHP-FRCC specimens under sustained tensile and bending loads up to 28 days. Under uniaxial tension, the load is applied to dog-bone type specimens. In the case of bending creep test, a sustained load is applied to a pair of prismatic specimens in a 4-point bending setup. The results show that UHP-FRCC exhibits low creep deformation under both these loading conditions. Furthermore, deflection hardening behavior lasts under Cracking behavior in terms of crack width and number of cracks under sustained loads in both composites is also studied and their comparisons are presented in the paper.